Antiretroviral prescription, retention in care and viral suppression by place of birth among adults with diagnosed HIV in the United States—2015–2017, medical monitoring project. Issue 1 (2nd January 2021) - Demeke, Hanna B.; Luo, Qingwei; Beer, Linda; Weiser, John
ABSTRACT: HIV clinical outcomes have not been fully assessed by place of birth at the national level. We analyzed the Medical Monitoring Project data, an annual cross-sectional survey designed to produce nationally representative estimates on adults with diagnosed HIV in the United States, collected during 2015–2017 ( n  = 7617). We compared sociodemographic, behavioral, and clinical outcomes by place of birth using Rao-Scott chi-square tests ( P  < .05). Overall, 13.6% of adults with diagnosed HIV were non-US-born. During the past 12 months, a higher percentage of non-US-born than US-born adults, respectively, were prescribed ART (89.4% vs. 84.1%), retained in care (87.1% vs. 80.0%), virally suppressed at the last test (77.2% vs. 70.9%), and had sustained viral suppression (70.9% vs. 63.3%). A lower percentage of non-US-born adults reported binge drinking (13.0% vs. 16.1%), using non-injection drugs (15.3% vs. 31.7%), and suffering from depression (15.9% vs. 23.3%) or anxiety (10.0% vs. 20.2%). A significantly higher percentage of non-US-born adults had Ryan White HIV/AIDS Program (RWHAP) coverage (54.4% vs. 43.1%) and attended a RWHAP-funded health care facility (73.9% vs. 66.6%). Factors contributing to better HIV clinical outcomes among non-US-born persons may include access to RWHAP coverage, lower levels of substance use, and better mental health.